Development of Reflectarray Antenna with Twin Cut Resonator for High Gain X Band Applications - N., Sivasankari; K., Abishek; J., Jerry Abraham (IRO Journal on Sustainable Wireless Systems, 2025)
This paper presents a high-gain reflect array antenna design that utilizes a double-cut ring structure to enhance performance in terms of gain and bandwidth. Reflect array antennas are recognized for their lightweight, low-profile characteristics and capability to achieve high directivity. However, their performance is often constrained by the phase shift range and accuracy of the reflecting elements. To overcome these limitations, the proposed design incorporates an innovative double-cut ring element structure, which improves phase control across a broad frequency range, resulting in enhanced beam-steering capabilities and increased gain. The double-cut ring structure is optimized to achieve a substantial phase shift range, contributing to the antenna's high-gain performance by facilitating precise phase correction throughout the array. The proposed structure illustrates the effectiveness of the double-cut ring configuration as a viable solution for improving the gain and operational bandwidth of reflect array antennas. The maximum gain achieved is 44.5 dBi at 10 GHz, and the Voltage Standing Wave Ratio (VSWR) plot indicates a value of 1.04 at the resonant frequency of 10 GHz.
Keywords: High-Gain Reflect Array Antenna; Double-Cut Ring Structure; Phase Control; Beam-Steering; Bandwidth Improvement; VSWR